Severe, Treatment-Refractory Periodontitis and Vitamin D Deficiency: A Multidisciplinary Case Report - Figliuzzi Michele Mario; Parentela Luca; Aiello Domenico; Altilia Simone (Case Reports in Dentistry)
Introduction. Vitamin D deficiency and periodontitis are common diseases among people. These conditions interact with each other and worsen the patient’s health. Modern dentistry aims to rehabilitate oral health and bring it back to the original state or even improve aesthetics. Without analysing the general health conditions of patients and without a multidisciplinary approach, it is sometimes not possible to solve a case such as we describe. This study shows how a vitamin D deficit can influence the choice of dental treatment. The patient, a 40-year-old woman, in generally good health, came to our observation complaining about pain during mastication, and profuse bleeding during home hygiene maneuvers. She wished to solve this situation. Materials and Methods. Since the patient did not respond well to the initial periodontal therapy, we carried out some accurate research concerning the patient’s previous clinical history, and as we suspected that a vitamin D deficit might be involved, a chemical test for vitamin D was carried out and the results confirmed our suspicions. The team programmed the following therapeutical plan: Phase 1—rehabilitation of normal values of vitamin D with the support of an endocrinologist; Phase 2—full mouth disinfection; Phase 3—periodontal surgical restorative therapy; and Phase 4—orthodontic therapy and fixed prosthetics rehabilitation. Results. The results for this clinical case were extremely satisfying; we were able to bring the periodontal illness under control; resolve the orthodontic problems; and rehabilitate the patient both functionally and aesthetically. Conclusion. Thanks to the collaboration and communication between specialists from different sectors of medicine and dentistry, the clinical case was solved with absolutely satisfactory results.